STUDI HISTOLOGI USUS BESAR SAPI BALI - Suwiti, Ni Ketut; Setiasih, Ni Luh Eka; Suastika, I Putu; Piraksa, I Wayan; Susari, Ni Nyoman Werdi (Buletin Veteriner Udayana; Vol. 2 No. 2 Agustus 2010)
A Study to detect the microscopic structure of large intestine (caecum, colon, rectum) ofbali cattle has been carried out. The samples were collected from 20 of bali cattle in Pesanggaran abattoir, Denpasar. The tissue samples were fixed, dehydrated and embeddedin paraffin and 4-5 mm sections. Harris-Haematoxilin-Eosin staining method, using toidentified of histological structure. Microscopic analysis was performed using binocularlight microscope (100 x, 450x). The study showed that the wall of the caecum, colon, andrectum are made up of four layers : mucosae, submucosae, muscularis externa, and serosa.The lined by mucosae ephitelium of simple columnar cells. The thick of mucosaare 29,9 ± 5,0 mm (caecum) 37,5 ± 8,4 mm (colon) and 58,9 ± 9,5 mm (rectum)respectively. The submucosae contain connective tissue and thick of these layerare 54,8 ± 8,8 mm; 21,2 ± 7,1 mm; and 16,5 ± 4,5 mm respectively. The muscularis externaconsists of two layers of smooth muscle inner circular and outer longitudinal. The thick ofthe mucularis externa are 98,5 ± 15,4 mm; 166,9 ± 44,4 mm; and 479 ± 28,6 mmrespectively. The serosa forms the outermost layer with thick 29,5 ± 8,5 mm;20,9 ± 7,6mm; and 12,1 ± 3,6 mm respectively. We observed for the presence richof Goblet cells and few limphatic nodules (Peyer’s patches) but no showed villi.
Keywords: histological structure, caecum, colon, rectum, bali cattle, limphatic nodules